Biological pathways via which the anthocyanin malvidin alleviated the murine colitis induced by Citrobacter rodentium. Issue 2 (23rd December 2022) - Liu, Fang; Smith, Allen D.; Wang, Thomas T. Y.; Pham, Quynhchi; Cheung, Lumei; Yang, Haiyan; Li, Robert W.
Abstract : Enteropathogenic E. coli (EPEC) is a causal agent for diarrheal diseases and contributes to morbidity and mortality in children under the age of five years. Abstract : Enteropathogenic E. coli (EPEC) is a causal agent for diarrheal diseases and contributes to morbidity and mortality in children under the age of five years. The emergence and rapid spread of antibiotic resistant EPEC strains necessitate the search for novel alternatives to antibiotics. In this study, we used Citrobacter rodentium, a natural mouse pathogen that mimics many aspects of human EPEC infections, to investigate the antimicrobial properties of the blueberry anthocyanin malvidin 3-glucoside (MG) using a multi-omics approach. MG supplementation reversed the bodyweight loss induced by C. rodentium infection and improved colonic hyperplasia and histopathological scores. In the colon tissue, MG supplementation significantly increased the expression of Hace1, a key regulator of TNFα-driven signaling, and impacted multiple pathways, such as TGFβ signaling. MG partially restored C. rodentium -induced microbial dysbiosis and significantly enhanced the abundance of the probiotic Bifidobacterium animalis . Moreover, MG disrupted the interactions of E. coli with other gut microbes. MG significantly mediated several host- and microbiota-derived metabolites, such as cytosine, ureidopropionic acid, and glutaric acid. MG normalized the bioactive lipid oleoylethanolamine, a member of the endocannabinoid system, from the dysregulated level in infected mice, directly contributing to its overall beneficial effects. Our findings provided novel insights into molecular processes via which the flavonoid malvidin exerts its biological effects in the gastrointestinal tract.